Fentanyl Inhibits Air Puff-Evoked Sensory Information Processing in Mouse Cerebellar Neurons Recorded in vivo - Yang, He-Min; Zhan, Li-Jie; Lin, Xue-Qin; Chu, Chun-Ping; Qiu, De-Lai; Lan, Yan (Frontiers in Systems Neuroscience, 2020)
Aim: To examine the effects of fentanyl, a potent mu-opioid receptor (MOR) agonist, on air puff-evoked responses in Purkinje cells (PCs) and molecular layer interneurons (MLIs) using in vivo patch-clamp recordings in anesthetized mice. Methods: Male mice 6-8 weeks-old were anesthetized and fixed on a custom-made stereotaxic frame. The cerebellar surface was exposed and perfused with oxygenated artificial cerebrospinal fluid (ACSF). Patch clamp recordings in cell-attached mode were obtained from PCs and MLIs. Facial stimulation by air-puff of the ipsilateral whisker pad was performed through a pressurized injection system. Fentanyl citrate, CTOP and H-89 dissolved in ACSF were perfused onto the cerebellar surface. Resluts: Fentanyl significantly inhibited the amplitude and area under the curve (AUC) of sensory stimulation-evoked inhibitory responses in PCs. Although fentanyl did not influence the frequency of simple spikes (SS), it decreased the pause of SS. The IC50 of the fentanyl-induced suppression of P1 response amplitude was 5.53 μM. The selective MOR antagonist CTOP abolished fentanyl-induced inhibitory responses in PCs. However, application of CTOP alone increased the amplitude, AUC of P1 and the pause of SS. Notably, fentanyl significantly inhibited the tactile-evoked response of MLIs, but did not affect their spontaneous firing. The fentanyl-induced decrease of inhibitory responses in PCs was partially prevented by a PKA inhibitor, H-89. Conclusions: These results suggest that fentanyl binds to MORs in MLIs to reduce GABAergic neurotransmission in MLI-PC projections and one potential mechanism is via modulation of the cAMP-PKA pathway.